Audio recordings dataset of grazing jaw movements in dairy cattle - Vanrell, Sebastián Rodrigo (2022)
This dataset is composed of correlated audio recordings and labels of ingestive jaw movements performed during grazing by dairy cattle. Using a wireless microphone, we recorded sounds of three Holstein dairy cows grazing short and tall alfalfa and short and tall fescue. Two experts in grazing behavior identified and labeled the start, end, and type of each jaw movement: bite, chew, and chew-bite (compound movement). For each segment of raw audio corresponding to a jaw movement we computed four well-known features: amplitude, duration, zero crossings, and envelope symmetry. These features are in the dataset and can be used as inputs to build automated methods for classification of ingestive jaw movements. Cow’s grazing behavior can be monitored and characterized by identifying and analyzing these masticatory events.